Demographic and clinical characteristics of inpatient stroke patients in Turkey - Geler Külcü, Duygu; Kuran, Banu; Yavuz Karahan, Ali; Özgirgin, Neşe; Başaran, Sibel; Yalıman, Ayşe; Savaş, Serpil; Tıkız, Canan; Aktaş, İlknur; Bardak, Ayşenur; Tuncer, Tiraje; Yılmaz, Figen; et al. (Turkish journal of physical medicine and rehabilitation, 2022)
Objectives: This study aims to assess the stroke rehabilitation facilities provided by university hospitals (UHs) and training and research hospitals (TRHs) and to evaluate the geographical disparities in stroke rehabilitation. Patients and methods: Between April 2013 and April 2014 a total of 1,529 stroke patients (817 males, 712 females; mean age: 61.7±14.0 years; range, 12 to 91 years) who were admitted to the physical medicine and rehabilitation clinics in 20 tertiary care centers were retrospectively analyzed. Demographic, regional and clinical characteristics, details of rehabilitation period, functional status, and complications were collected. Results: The median duration of stroke was five (range, 1 to 360) months. The ratio of the patients treated in the TRH in the Marmara region was 77%, but only 25% of the patients were living in the Marmara region. Duration of hospitalization was longer in the TRHs with a median of 28 days compared to those of UHs (median: 22 days) (p<0.0001). More than half of the patients (55%) were rehabilitated in the Marmara region. Time after stroke was the highest in the Southeast region with a median of 12 (range, 1 to 230) months and the lowest in the Aegean region with a median of four (range, 1 to 84) months. Conclusion: This study provides an insight into the situation of stroke rehabilitation settings and characteristics of stroke patients in Turkey. A standard method of patient evaluation and a registry system may provide data about the efficacy of stroke rehabilitation and may help to focus on the problems that hinder a better outcome.